EP.TH.515A Case of mucinous adenocarcinoma of the breast in a young male patient presenting with a subcutaneous axillary lump. (28th October 2021) - Suliman, Amna; Latif, Ahmed; Metafa, Anna; Uhercik, Michal
Abstract: Aims: Mucinous adenocarcinoma of the breast is rarely encountered clinically, and makes up only 0.01% of Breast cancer (BC) cases and < 1% of male breast cancer (MBC). We describe an extremely rare case of mucinous carcinoma in accessory axillary breast tissue in a male. Case details: A 48-year old male presented with a subcutaneous lump in his left axilla. Ultrasound described a 30mm hypoechoic mass and core biopsy confirmed mucinous adenocarcinoma, strongly positive for oestrogen and progesterone receptors, HER2 negative. A solitary enlarged axillary node in was sampled (C2) and mammogram reported a 32mm spiculate mass (M4) on the left. PET scan showed uptake only in the known axillary mass. Management: Wide Local Excision and Sentinel Lymph Node Biopsy (SLNB) was completed. Histology showed a 27 mm grade 2 mucinous carcinoma, and the patient completed adjuvant radiotherapy and was commenced on tamoxifen. Conclusions: MBC is rare, and accounts for only 1% of all BC. Men tend to be diagnosed at an older age (mean is 67 years) and usually have genetic/hormonal risk factors. Histologically, invasive ductal carcinoma makes up 95% of MBC. In every regard therefore, our case breaks the mold since, he was young, had no genetic/family history and no background of gynaecomastia (present in 6-38%). Literature review suggests that this is only the second case of its kind and from it we can learn to be vigilant for MBC in accessory axillary breast tissue as well as the more typical presentations.